The contenders : the rise of the Pacific powers - Livingstone, J. M., 1925- (Cassell, 1998)
The traditional dominance of the United States in the business communities of the Pacific region can no longer be taken for granted. Japan, Korea and, increasingly, China are the main contenders. These are nations which have the potential to take control of this lucrative region and change the face of world commerce for ever. In this fascinating and scholarly study, James M. Livingstone systematically explores the industrial, cultural and political background of every key country in the region. It is only through a better understanding of the region that other nations will be able to anticipate future developments and participate fully in them.